2015
DOI: 10.1007/s13277-015-3498-8
|View full text |Cite
|
Sign up to set email alerts
|

FOXP4 modulates tumor growth and independently associates with miR-138 in non-small cell lung cancer cells

Abstract: Family of forkhead box transcription factors, including forkhead box P4 (FOXP4), plays an important role in oncogenesis. The current study is to evaluate the role of FOXP4 in regulating human non-small cell lung cancer (NSCLC). Quantitative RT-PCR and Western blot were performed to evaluate the gene and protein expressions of FOXP4 in six NSCLC cell lines and 55 NSCLC patients. Lentivirus of small hairpin RNA (FOXP4-shRNA) was used to downregulate FOXP4 in NSCLC cell lines A549 and H1703 cells. Its effect on N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…FOXP4 encodes a transcription factor (forkhead box P4) expressed in proximal and distal airway epithelium as well as in subepithelial mesenchyme during lung development [20]. FOXP4 is also expressed in CD4+ and CD8+ T cells and appears to contribute to cytokine production and memory T cell responses [21], and a recent study reported FOXP4 as an important regulator of non-small cell lung cancer cells [22]. The specific role of this locus in disease pathogenesis requires further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…FOXP4 encodes a transcription factor (forkhead box P4) expressed in proximal and distal airway epithelium as well as in subepithelial mesenchyme during lung development [20]. FOXP4 is also expressed in CD4+ and CD8+ T cells and appears to contribute to cytokine production and memory T cell responses [21], and a recent study reported FOXP4 as an important regulator of non-small cell lung cancer cells [22]. The specific role of this locus in disease pathogenesis requires further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, knockdown of FOXP4 was shown to markedly reduce the proliferation and invasion capabilities of A549 and H1703 cells and induce cell cycle arrest. These findings further confirm that FOXP4 is target gene for miR‐138 …”
Section: Discussionmentioning
confidence: 99%
“…Huang et al showed that FOXP3 downregulates miR-142-3p to keep the adenylyl cyclase (AC) 9 / cAMP pathway active in T REG cells [152]. In addition, miR-138 is an upstream regulator of FOXP4 and directly regulates FOXP4 expression in NSCLC [153]. Similarly, it was also found that miR-338-3p inhibits HCC cell growth by targeting FOXP4 [154].…”
Section: Fox-related Mirnasmentioning
confidence: 99%